(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
During the early development of personality emotional bonding is very important. The ties of close emotional relationship are formed. Children gradually learn about the world close to them and they get emotionally tied to their environment. The significant persons, the places and the objects are of great importance, in addition attachment to activities also get a big role. Game activites have great importance all along childhood. In this study primary personal ties are analysed, object-related ties are explained. The development of play and the relationship of children to game activities and toys are considered. An empirical research was conducted and its results are presented.